140k views
4 votes
(2x-10)(x+3)+(x3+1)(x-4) what does it equal to

2 Answers

1 vote

Answer:

Use the FOIL method.

(2x - 10)(x + 3) = 2x*x + 2x*3 + (-10)*x + (-10)*3

= 2x² + 6x - 10x - 30 {Combine like terms}

= 2x² - 4x - 30

(x³ + 1)(x - 4) = x³*x + x³ *(-4) + 1*x + 1*(-4)

= x⁴ - 4x³ + x - 4

(2x - 10)(x +3) +(x³ +1)(x - 4) = 2x² - 4x - 30 + x⁴ - 4x³ + x - 4

Combine like term

= x⁴ - 4x³ + 2x² - 4x + x -30 - 4

= x⁴ - 4x³ + 2x² - 3x - 34

Explanation:

por nada!!!

User PrasadU
by
5.6k points
0 votes

Answer:

Explanation:

Use FOIL method.

(2x - 10)(x + 3) = 2x*x + 2x*3 + (-10)*x + (-10)*3

= 2x² + 6x - 10x - 30 {Combine like terms}

= 2x² - 4x - 30

(x³ + 1)(x - 4) = x³*x + x³ *(-4) + 1*x + 1*(-4)

= x⁴ - 4x³ + x - 4

(2x - 10)(x +3) +(x³ +1)(x - 4) = 2x² - 4x - 30 + x⁴ - 4x³ + x - 4

Combine like term

= x⁴ - 4x³ + 2x² - 4x + x -30 - 4

= x⁴ - 4x³ + 2x² - 3x - 34

User Indra
by
5.4k points